The Position of Inheritance of Children from Marriages Which Not Recorded in the Conception of Legal Certainty - Novita, Puteri Mela; Bawono, Bambang Tri; Hafidz, Jawade (Jurnal Konstatering, 2022)
This study aims to determine and analyze the inheritance position of children from marriages that are not registered in the conception of legal certainty, analyze legal protection for children from unregistered marriages and analyze examples of certificates of inheritance rights. The approach method in this research was a normative juridical approach, the research specification was descriptive analytical. The data required included secondary data taken by the literature study method. The data analysis method used descriptive qualitative analysis method. Based on the research, it is concluded that the position of inheritance of children from marriages that are not registered according to the Marriage Act is only obtained from the mother and her mother's family, on the position of inheritance if the child is recognized by the father as his biological parent then he is entitled to the position of inheritance. In principle, children from marriages are not registered with the decision of the Constitutional Court Number 46/PUU-VIII/2010, children from marriages are not registered to obtain legal certainty of their civil rights. Legal protection for children from marriages is not recorded. Legal efforts can be taken so that a child born from a marriage that is not registered obtains a position as a legal child for a Muslim couple by applying for Marriage Istbat to the Religious Court, so that the Religious Court legalizes the marriage, while for couples non-Muslims to register their marriage with the Civil Registry Office. So that they can issue a marriage certificate and the child from the marriage becomes a legal child and obtains legal protection.